Photoluminescence in carbon-doped GaAs grown by atmospheric-pressure metalorganic chemical vapor deposition - Cho, SH; Kim, EK; Min, SK (KOREAN PHYSICAL SOC, 1998)
The effect of the band gap narrowing induced by the thermal perturbation in carbon-doped GaAs epilayers was determined by using photoluminescence (PL) spectroscopy. The GaAs epilayers were grown on semi-insulating GaAs substrates by atmospheric-pressure metalorganic chemical vapor deposition. The PL measurements were performed in a closed-cycle refrigerator in the temperature range from 16 to 250 K. The measured peak energy and band gap of the PL spectrum shift to lower energy, and the full width at half maximum (FWRM) increases with increasing temperature. The thermal shifts of the peak energy and the band gap are well described by the Varshni equation. The results suggest that the effective band gap at T=0 K can be inferred from measurements of the hole concentration. The change in the FWHM of the PL spectrum as a function of temperature T can be expressed by Delta f(T) = f(T) - f(20 K) similar to T-1/2.
Keywords: GAP; SEMICONDUCTORS; TEMPERATURE; LUMINESCENCE; SPECTROSCOPY